A Study On The Address System Used In Thriller Movie And Its Subtitle - Ependi, Siti Sulastri (2012)
This study aims at describing the variations of address systems used in the thriller movie and its subtitle, describes reasons of using each variation of address systems used in the thriller movie and its subtitle and clarify the equivalences of the reasons of address systems used in thriller movie. The type of this research is descriptive qualitative research which takes a document oriented as the method of collecting data. By this method, the writer uses thriller movie subtitle entitled Orphan, Black Swan, and Drive Angry as the data source, and the data taken are English and Indonesian address system. The variations of address system refers to Tu and Vous theory and the reasons of variations of address systems refers to Dell Hyme's SPEAKING theory. The result of the research show that firstly, the variations of address system come into 12 types; first name, full name, intimate name, kinship name, solidarity name, mockery name, title, title plus first name, title plus last name, profession, respect and unfamiliar term. Secondly, there are 8 reasons in using address system; showing intimacy, showing anger, showing anxiety, showing mockery, showing power, showing respectful, showing solidarity, showing unfamiliarity. Lastly, the equivalent of the reasons; there are 38 data or 84,44% are equivalent and 7 data or 15,55% are not equivalent.